Article Withdrawal by ASERS Publishing - Fraudulent double submission and legal limitations - Environmental Problems of Processing Industry in the Agro-Industrial Complex of the Region - GLOTKO, Andrey; SYCHEVA, Irina; PETROVA, Lyudmila; VOROZHEYKINA, Tatiana; TOLMACHEV, Alexey; ISLAMUTDINOVА, Dina (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019DO - 10.14505//jemt.v10.5(37).04, 2019)
The theoretical grounding of the management system of animal feedingstuff milling of the region was performed. The facilities of animal feedingstuff milling are divided according to the degree of independence of business conducting and directions of sales of the products manufactured. The factors of the internal and external environment of the animal feedingstuff milling of the region were considered. The analysis was performed and the tendencies in the development of animal feedingstuff milling of the region and the system of its management were revealed; the directions of the development of animal feedingstuff milling of the agrarian region were grounded. The potential capacity of the regional market of animal feedingstuff for livestock breeding of the region was calculated. It was offered to form the body of economic management in the form of an independent legal entity bearing the responsibility for execution of the functions imposed on it to develop and implement the plan of development of animal feedingstuff milling – JSC Animal Feedingstuff Cluster of the Altai Territory.